Effect of swearing on strength and power performance - Stephens, R.; Spierer, D. K.; Katehis, E. (Psychology of Sport and Exercise, 2018)
Objectives: Swearing aloud increases pain tolerance. The hypothesis that this response may be owed to an increase in sympathetic drive raises the intriguing question as to whether swearing results in an improvement in strength and power. Design: Employing repeated measures designs, we evaluated the effect of repeating a swear word v. a neutral word on strength and power during anaerobic and isometric exercise through two experiments. Method: Experiment #1 (n = 29) employed the Wingate Anaerobic Power Test (WAnT). Experiment #2 (n = 52) employed an isometric handgrip test. Results: Greater maximum performance was observed in the swearing conditions compared with the non-swearing conditions for WAnT power (Experiment #1; dz = 0.618, p = 0.002) and hand grip strength (Experiment #2; dz = 0.962, p < 0.001). However, swearing did not affect cardiovascular or autonomic function assessed via heart rate, heart rate variability, blood pressure and skin conductance. Conclusions: Data demonstrate increased strength and power performance for swearing v. not swearing but the absence of cardiovascular or autonomic nervous system effects makes it unclear whether these results are due to an alteration of sympathovagal balance or an unknown mechanism.